Manifestation of the Spin in the Isotope Effects - Plekhanov V. G.; Myshkin (Mishkin) V. F. Vyacheslav Fedorovich; Khan V. A. Valery Alekseevich; Izhoykin D. A. Dmitry Aleksandrovich (Plasma, Microwave, Ion, Electron and Isotope Technologies, 2015)
Title screen